Analysis of Community Perception Towards Sharia Banking in North Sumatra - Onan Marakali Siregar; Selwendri Selwendri; M B Abdillah (Universitas Negeri Medan, 2020)
The banking industry in Indonesia is increasingly crowded with the emergence of banks operating under sharia principles. Although in general almost all banking products offered by Sharia banking and conventional commercial banks are relatively the same, in reality they both have different operational principles, especially in terms of efforts to obtain profits. In addition, the development between Sharia banking is not as expected given the population of Indonesia, which is predominantly Muslim. Sharia banking are far behind conventional banks. The aim of the research was to find out the perceptions of the people of North Sumatra on Islamic banking through surveys in 4 major cities namely Medan, Binjai, Langkat and Deli Serdang which were considered to represent the Muslim population in North Sumatra. This study used a quantitative descriptive survey and study . The survey is used to obtain a comprehensive picture of people's perceptions of Islamic banking in North Sumatra. Quantitative descriptive study, used to explore strategies and considerations used by Islamic banking to the community.The results of the study show that the three independent variables have an influence and it can be seen that the service variable is the main variable that contributes most to its relationship with the results of public perception on the two research objects on Banking.